Investigation of Mechanical Properties and Phase Transformations of Al84Y10Ni4Co2 Alloy Produced by Rapid Solidification - Gögebakan, Musa (Fırat University, 2025)
In the current study, Al84Y10Ni4Co2 alloy was obtained as amorphous ribbons by rapid solidification method. Phase identification of the alloy were examined by X-ray diffraction (XRD), and thermal properties such as, phase transformation temperatures and activation energy were examined by differential scanning calorimetry (DSC). The mechanical properties of the alloy at room temperature and high temperatures were examined by Vickers microhardness (HV) measurement. XRD results showed that the alloy produced by rapid solidification had an amorphous structure. However, at temperatures above 544 ?K, phase transformation occurred and the alloy became crystalline. DSC results show that the crystallization onset temperature (Tx) of the amorphous Al84Y10Ni4Co2 alloy was 544 ?K, the alloy exhibits a distinct glass transition temperature (Tg) and a large supercooled liquid region (?Tx) before crystallization. Tg and ?Tx values of amorphous Al84Y10Ni4Co2 alloy were measured as 511 ?K and 33 ?K, respectively. The activation energy of the crystallization peak was determined with the Kissinger equation and found to be 258 kJ/mol. The hardness value of the amorphous alloy at room temperature was measured as 388 HV. The microhardness value increased as a result of thermal treatment and reached 564 HV at 550 ?K. The hardness value of the alloy decreased at temperatures higher than 550 ?K and the alloy became brittle.

Mevcut çalışmada, Al84Y10Ni4Co2 alaşımı hızlı katılaştırma yöntemiyle amorf şeritler halinde üretilmiştir. Alaşımın faz tanımlaması, X-ışını difraksiyonu (XRD) ile, faz dönüşüm sıcaklıkları ve aktivasyon enerjisi gibi ısıl özellikleri diferansiyel taramalı kalorimetre (DSC) ile belirlenmiştir. Alaşımın oda sıcaklığındaki ve yüksek sıcaklıklardaki mekanik özellikleri Vickers mikrosertlik (HV) ölçümü yapılarak incelenmiştir. XRD sonuçları, hızlı katılaştırma ile üretilen alaşımın amorf yapıda olduğunu göstermiştir. Ancak, 544 ?K’nin üzerindeki sıcaklıklarda faz dönüşümü gerçekleşmiş ve alaşım kristal yapıya dönüşmüştür. DSC sonuçlarına göre, amorf Al84Y10Ni4Co2 alaşımının kristalleşme başlangıç sıcaklığı (Tx) 544 ?K olup, kristalleşmeden önce belirgin bir camsı geçiş sıcaklığı (Tg) ve geniş bir aşırı soğutulmuş sıvı bölgesi (?Tx) sergilediği görülmüştür. Alaşımın Tg ve ?Tx değerleri sırasıyla 511 ?K ve 33 ?K olarak ölçülmüştür. Kristalleşme pikine ait aktivasyon enerjisi Kissinger yöntemiyle hesaplanmış ve 258 kJ/mol olarak bulunmuştur. Amorf alaşımın oda sıcaklığındaki mikrosertlik değeri 388 HV olarak ölçülmüştür. Mikrosertlik değeri ısıl işlem sonucu artarak 550 ?K’de 564 HV değerine ulaşmıştır. 550 ?K’den daha yüksek sıcaklıklarda mikro sertlik değeri azalmış ve alaşım gevrek hale gelmiştir.
Hızlı Katılaştırma ile Üretilen Al84Y10Ni4Co2 Alaşımının Mekanik Özelliklerinin ve Faz Dönüşümlerinin İncelenmesi
Keywords: Physical Metallurgy; Fiziksel Metalurji; Material Characterization; Malzeme Karekterizasyonu; Metals and Alloy Materials; Metaller ve Alaşım Malzemeleri; Manufacturing Metallurgy; Üretim Metalurjisi